Coordinated pyruvate kinase activity is crucial for metabolic adaptation and cell survival during mitochondrial dysfunction. Issue 21 (24th June 2021) - Zhou, Xiaoshan; Mikaeloff, Flora; Curbo, Sophie; Zhao, Qian; Kuiper, Raoul; Végvári, Ákos; Neogi, Ujjwal; Karlsson, Anna
Abstract: Deoxyguanosine kinase (DGUOK) deficiency causes mtDNA depletion and mitochondrial dysfunction. We reported long survival of DGUOK knockout ( Dguok −/− ) mice despite low (<5%) mtDNA content in liver tissue. However, the molecular mechanisms enabling the extended survival remain unknown. Using transcriptomics, proteomics and metabolomics followed by in vitro assays, we aimed to identify the molecular pathways involved in the extended survival of the Dguok −/− mice. At the early stage, the serine synthesis and folate cycle were activated but declined later. Increased activity of the mitochondrial citric acid cycle (TCA cycle) and the urea cycle and degradation of branched chain amino acids were hallmarks of the extended lifespan in DGUOK deficiency. Furthermore, the increased synthesis of TCA cycle intermediates was supported by coordination of two pyruvate kinase genes, PKLR and PKM, indicating a central coordinating role of pyruvate kinases to support the long-term survival in mitochondrial dysfunction.